Analisis Penerapan GMP dan SSOP pada Produksi Amplang Ikan Tenggiri di Desa K, Kecamatan Selakau, Kabupaten Sambas - Mulpi Iman Saputra; Nurleli Nurleli; Rifky Kurniawan; Vika Dwi Pratiwi (Journal of Fisheries and Marine Applied Science, 2025)
The purpose of this study was to implement the Sanitation Standard Operating Procedure (SSOP) and Good Manufacturing Practice (GMP) in the Amplang mackerel fish company in Selakau District, Sambas Regency. This study was conducted through direct observation and interviews using a checklist made by SSOP and GMP. The results of the study indicate that the implementation of SSOP and GMP is still not ideal, and there are still many aspects that need to be improved. Although the industry has a P-IRT permit and is located close to the source of raw materials, there are several problems that hinder the implementation of SSOP and GMP. These include the layout and cleanliness of the production building, inadequate sanitation facilities, process control and documentation, water supply quality, employee hygiene, and management of production equipment. Improvements in these elements are essential to improve production safety. Improving the understanding of business owners and employees about the importance of implementing SSOP and GMP is also an important part of the improvement effort. To meet food safety standards and ensure product quality, improvements are needed in various aspects. To ensure the safety and quality of mackerel fish crackers products, this study suggests better implementation of SSOP and GMP.